Real-Time Validation of a Decoupled Control Strategy for Back-To-Back Modular Multilevel Converter in Low Frequency Transmission - Espina-Gonzalez, E; Diaz-Diaz, M; Valdivia-Lefort, P (Institute of Electrical and Electronics Engineers Inc., 2024)
The Modular Multilevel Converter is a device that transforms alternating current into direct current and has gained popularity in high voltage transmission due to its modularity, efficiency, and controllability. Recently, configurations of this converter have been proposed for applications like wind energy conversion systems and low-frequency alternating current transmission, where direct alternating current to alternating current conversion is required. However, controlling the converter in these applications presents significant challenges, as alternating current to alternating current operation can lead to voltage fluctuations. This work describes a decoupled control strategy for a modular multilevel converter operating at low frequency. This strategy utilizes circulating currents in each module to maintain acceptable ripple levels in the capacitor voltage of each cell. The effectiveness of this strategy is validated using real-time simulation models implemented with the OPAL-RT. © 2024 IEEE.